2021
DOI: 10.1371/journal.ppat.1009785
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt and altered cell-type specific DNA methylation profiles in blood during acute HIV infection persists despite prompt initiation of ART

Abstract: HIV-1 disrupts the host epigenetic landscape with consequences for disease pathogenesis, viral persistence, and HIV-associated comorbidities. Here, we examined how soon after infection HIV-associated epigenetic changes may occur in blood and whether early initiation of antiretroviral therapy (ART) impacts epigenetic modifications. We profiled longitudinal genome-wide DNA methylation in monocytes and CD4+ T lymphocytes from 22 participants in the RV254/SEARCH010 acute HIV infection (AHI) cohort that diagnoses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 73 publications
0
18
2
Order By: Relevance
“…study, that found, in a population of 22 individuals with acute HIV infection, that initiating ART restored less than 1% of the HIV-induced DNA methylation changes in monocytes and had no effect upon DNA methylation alterations in CD4 + T lymphocytes. 39 However, this discordancy in the impact of ART on DNA methylation dynamics might be consequence of the difference in the duration of ART between both studies (approximately 8 months against 96 weeks in the present study), and in differences in the two populations (primary infection versus chronic infection in the present study). Thus, this could indicate that the trend towards normalizing DNA methylation changes induced by HIV does not occur following the immediate initiation of ART, although more longitudinal data are needed to confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 53%
“…study, that found, in a population of 22 individuals with acute HIV infection, that initiating ART restored less than 1% of the HIV-induced DNA methylation changes in monocytes and had no effect upon DNA methylation alterations in CD4 + T lymphocytes. 39 However, this discordancy in the impact of ART on DNA methylation dynamics might be consequence of the difference in the duration of ART between both studies (approximately 8 months against 96 weeks in the present study), and in differences in the two populations (primary infection versus chronic infection in the present study). Thus, this could indicate that the trend towards normalizing DNA methylation changes induced by HIV does not occur following the immediate initiation of ART, although more longitudinal data are needed to confirm this hypothesis.…”
Section: Discussioncontrasting
confidence: 53%
“…Although lentiviral infections have been shown to specifically alter these parameters 54 – 57 , disruptions to butyrate-responsive pathways may not be the primary roadblock to complete immune restoration. Lentiviral infections induce widespread epigenetic changes 58 , 59 , many of which persist or rise anew after the initiation of ARV therapy 60 63 . Although HDAC inhibitors have been successfully used to reactivate viral reservoirs in latency reversal studies 64 66 , sodium butyrate treatment was not associated with increased viremia in our study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a recent study that demonstrated certain epigenetic changes induced upon acute HIV-1 infection not to revert upon ART. 39 …”
Section: Resultsmentioning
confidence: 99%